Selection of the best healthcare waste disposal techniques during and post COVID-19 pandemic era. (25th January 2021) - Manupati, Vijaya Kumar; Ramkumar, M.; Baba, Vinit; Agarwal, Aayush
Abstract: In recent years, municipal authorities especially in the developing nations are battling to select the best health care waste (HCW) disposal technique for the effective treatment of the medical wastes during and post COVID-19 era. As evaluation of various disposal alternatives of HCW and selection of the best technique requires considering various tangible and intangible criteria, this can be framed as multi-criteria decision-making (MCDM) problem. In this paper, we propose an assessment framework for the selection of the best HCW disposal technique based on socio-technical and triple bottom line perspectives. We have identified 10 criteria on which the best HCW disposal techniques to be selected based on extant literature review. Next, we use Fuzzy VIKOR method to evaluate 9 HCW disposal alternatives. The effectiveness of the proposed framework has been demonstrated with a real-life case study in Indian context. To check the robustness of the proposed methodology, we have compared the results obtained with Fuzzy TOPSIS (Technique of Order Preference Similarity to the Ideal Solution). The results help the municipal authorities to establish a methodical approach to choose the best HCW disposal techniques. Our findings indicate that incineration is the best waste disposal technique among the available alternatives. Even if the dataset indicates 'incineration' is the best method, we must not forget about the environmental concerns arising from this method. In COVID time, incineration may be the best method as indicated by the data analysis, but "COVID" should not be an excuse for causing "Environmental Pollution". Highlights: Health care waste disposal technique selection is a serious concern during COVID-19. We propose Fuzzy VIKOR based method for selecting the best disposal technique. This work has been grounded on Triple Bottom Line and Socio-Technical perspectives. The proposed framework has been validated with a real-life case study. The effectiveness of the proposed method has been compared with Fuzzy TOPSIS.